Transcriptomic Analyses of Adipocyte Differentiation From Human Mesenchymal Stromal‐Cells (MSC). Issue 4 (12th July 2016) - Casado‐Díaz, Antonio; Anter, Jaouad; Müller, Sören; Winter, Peter; Quesada‐Gómez, José Manuel; Dorado, Gabriel
Abstract : Adipogenesis is a physiological process required for fat‐tissue development, mainly involved in regulating the organism energetic‐state. Abnormal distribution‐changes and dysfunctions in such tissue are associated to different pathologies. Adipocytes are generated from progenitor cells, via a complex differentiating process not yet well understood. Therefore, we investigated differential mRNA and miRNA expression patterns of human mesenchymal stromal‐cells (MSC) induced and not induced to differentiate into adipocytes by next (second)‐generation sequencing. A total of 2, 866 differentially expressed genes (101 encoding miRNA) were identified, with 705 (46 encoding miRNA) being upregulated in adipogenesis. They were related to different pathways, including PPARG, lipid, carbohydrate and energy metabolism, redox, membrane‐organelle biosynthesis, and endocrine system. Downregulated genes were related to extracellular matrix and cell migration, proliferation, and differentiation. Analyses of mRNA‐miRNA interaction showed that repressed miRNA‐encoding genes can act downregulating PPARG‐related genes; mostly the PPARG activator ( PPARGC1A ). Induced miRNA‐encoding genes regulate downregulated genes related to TGFB1 . These results shed new light to understand adipose‐tissue differentiation and physiology, increasing our knowledge about pathologies like obesity, type‐2 diabetes and osteoporosis. J. Cell. Physiol. 232: 771–784, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Adipogenesis transcriptomics was studied in mesenchymal stem‐cells (MSC) and 659 mRNA and 46 miRNA were upregulated in adipocyte differentiation. Metabolic, redox, and endocrinology process were upregulated in adipogenesis and Migration, proliferation, and differentiation to others cell types were downregulated. miRNA that can interact with PPARG and TGFB1 pathways were both downregulated and upregulated.